Quantitative damage evaluation of thermal barrier coatings subjected to tensile loading using an acoustic emission method - Yang, L.; Zhong, Z.; Zhou, Y.; Lu, Chunsheng (Nil, 2012)
The fracture process of thermal barrier coatings (TBCs) subjected to tensile loading is monitored using an acoustic emission (AE) method. The surface crack density is calculated based on a modified shear-lag model to obtain the quantitative correlation of damage in TBCs and AE parameters. The calculated crack density shows a well correlated relationship with AE events, which is well agreement with experimental results.